2011
DOI: 10.1140/epjd/e2011-20485-4
|View full text |Cite
|
Sign up to set email alerts
|

Matter rogue wave in Bose-Einstein condensates with attractive atomic interaction

Abstract: We investigate the matter rogue wave in Bose-Einstein Condensates with attractive interatomic interaction analytically and numerically. Our results show that the formation of rogue wave is mainly due to the accumulation of energy and atoms toward to its central part; Rogue wave is unstable and the decay rate of the atomic number can be effectively controlled by modulating the trapping frequency of external potential. The numerical simulation demonstrate that even a small periodic perturbation with small modula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(52 citation statements)
references
References 50 publications
0
51
0
1
Order By: Relevance
“…(16). In the following, we discuss in detail how the dark-dark RW structures get deformed for different forms of diffraction parameter β(z).…”
Section: Characteristics Of Dark-dark Rwsmentioning
confidence: 99%
“…(16). In the following, we discuss in detail how the dark-dark RW structures get deformed for different forms of diffraction parameter β(z).…”
Section: Characteristics Of Dark-dark Rwsmentioning
confidence: 99%
“…Therefore, it is of high significance to study the dynamics of RWs and breather profiles of the GP equation (1). However only few attempts have been made to identify and analyze the RWs and breather solutions of (1) [35][36][37][38][39][40]. To the best of our knowledge neither higher-order RW solutions (with certain free parameters) nor higher order breather solutions of (1) have been taken up for study.…”
Section: Introductionmentioning
confidence: 99%
“…The scaling behavior is similar to systems that are described by the Kibble-Zurek mechanism (45-47), although a key difference in our system is the presence of dissipation and collapse, which is not part of the Kibble-Zurek scenario. The ability to finely control the interaction between atoms, and the relatively slow timescale for dynamics point toward the study of rogue matterwaves (48,49), analogous to the rogue waves observed in optical systems (50), as a natural extension of this work. Our methods are additionally amenable to studying the formation and propagation of higher-order solitons, such as breathers (51,52).…”
Section: I /(2m)mentioning
confidence: 96%